2020
DOI: 10.1017/s0031182020001225
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of novel albendazole salt formulations against secondary cystic echinococcosis in experimentally infected mice

Abstract: In this study, we evaluated the efficacy, expressed as a mean weight decrease of the whole echinococcal cyst mass, of novel benzimidazole salt formulations in a murine Echinococcus granulosus infection model. BALB/c mice were intraperitoneally infected with protoscoleces of E. granulosus (genotype G1). At 9 months post-infection, treatment with albendazole (ABZ), ricobendazole (RBZ) salt formulations, and RBZ enantiomer salts (R)-(+)-RBZ-Na and (S)-(−)-RBZ-Na formulations were initiated. Drugs were orally appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…As for other chiral pharmaceutical molecules, the enantiomers of two sulfoxides may display different pharmacological properties. In this regard, in vivo studies showed that the antiparasitic activity of the (R)-ricobendazole enantiomer is higher than the (S)-ricobendazole counterpart [24]. Moreover, an accumulation of (R)-ricobendazole has been observed in the cerebrospinal fluid of patients with neurocysticercosis [31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for other chiral pharmaceutical molecules, the enantiomers of two sulfoxides may display different pharmacological properties. In this regard, in vivo studies showed that the antiparasitic activity of the (R)-ricobendazole enantiomer is higher than the (S)-ricobendazole counterpart [24]. Moreover, an accumulation of (R)-ricobendazole has been observed in the cerebrospinal fluid of patients with neurocysticercosis [31].…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that we included in the series of tested molecules two couples of enantiomers derived from the corresponding two chiral benzimidazoles (i.e., ricobendazole and oxfendazole) to analyze whether they could have distinct effects on the viability of the aforementioned cancer cell lines based on the stereoselective metabolism involving this organic scaffold (Figure 1). In the series, we also tested the antiproliferative activities against parasites of new benzimidazole salt formulations, recently licensed by some of us, which demonstrated improved bioavailability and solubility in vivo, in studies against secondary cystic echinococcosis using experimentally infected mice [24]. Remarkably, these patented salts were prepared to overcome the issues related to the poor aqueous solubility of the benzimidazole scaffold and the corresponding erratic bioavailability, as previously explored also by other authors through several strategies, including the inclusion in cyclodextrin complexes [25,26], the transformation into soluble prodrugs [27], the characterization and use of selected polymorphic forms and solvates [28], and the preparation of innovative formulations [29].…”
Section: Introductionmentioning
confidence: 99%
“…They also found consistently lower drug concentrations in the cyst fluid compared to plasma samples, illustrating the problems to get the drug to the desired site of action, namely the interior of the parasite. Overall, these results are encouraging, since benzimidazole salts can be synthesized in a simple, cheap and rapid manner, they have an improved and more rapid anthelmintic activity than the conventional benzimidazoles, and are prone to cause less side-effects (Vural et al 2020).…”
Section: Improving Treatments By Improving the Solubility Of Benzimidazolesmentioning
confidence: 89%
“…A major caveat of this procedure is physiological adaptation, meaning that the biological characteristics of the metacestode might change due to adaption to the murine host. Different techniques have been developed that would allow in vitro culture of E. multilocularis metacestodes (Hemphill andGottstein, 1995, Jura et al, 1996). However, the major breakthrough that allowed to maintain and propagate metacestodes at a larger scale is the culture method established by Brehm and Spiliotis (Brehm and Spiliotis, 2009).…”
Section: Surgical Treatment Of Alveolar and Cystic Echinococcosismentioning
confidence: 99%
See 1 more Smart Citation